Comparison of canine and premolar root lengths between group function and canine guided occlusions - Moshaoa, Lerato (My University, 2016)
Background: During orthodontic treatment, the maxillary canines are commonly extruded to give a patient canine disocclusion, without the clinician having previously checked as to whether the presenting function was canine guided occlusion or group function occlusion. There is a general belief that the roots of canines are longer than premolars and therefore are able to better withstand occlusal forces than the other teeth. Aim: The aim of this research was to compare the root lengths of the canines and premolars between and within subjects with canine guidance (CG) and group function (GF). Methods: Root lengths of canines and premolars were measured on periapical radiographs and compared between and within subjects with CG and GF. Results: The canine roots were generally longer than those of the premolars in both groups. However, this difference was much greater in the CG group compared with GF. Premolar roots in GF were significantly longer than in CG. Conclusion: Canine and premolar root lengths are fairly similar in GF but not in CG, where the canine roots are much longer than premolars. The roots of premolars in GF occlusion are longer than those in CG occlusion. There is no difference in root lengths of the canines between CG and GF occlusions.
A research report submitted to the Postgraduate committee in partial fulfilment of the requirements for the degree of Master of Dentistry in the branch of Orthodontics Parktown, Johannesburg, South Africa 2016